THE MEDICAL PLANT USE IN FIGHTING PARASITOSIS AND INTESTINAL WORMS GOOD NEIGHBORHOOD IN THE GARDEN IN THE MUNICIPALITY BENJAMIN CONSTANT-AM, BRAZIL - Coelho, Diana Lopes; Brandão, Eliel Guimarães; Rosas, Lisandra Vieira; Lima, Renato Abreu; Pinto, Márcia Nascimento; Pantoja, Tatyanna Mariucha (South American Journal of Basic Education, Technical and Technological, 2016)
The use of medicinal plants with different therapeutic purposes is part of the popular knowledge, and the worms or intestinal parasites treated by such plants. Therefore, this study aimed to carry out an ethnobotanical survey of medicinal plants to combat parasitic diseases and intestinal worm infections in the neighborhood Bom Jardim in the municipality of Benjamin Constant AM. Structured questionnaires were applied with open and closed questions to 38 residents to verify the determining factors for the emergence of parasites and worms and the end of the research, produced a list of plant species with their most common uses. As a result, the monthly income is found, basic sanitation and water quality as possible factors contributing to the emergence of parasites and intestinal worms. In addition, it identified 35 different species of medicinal plants used for the treatment of parasites and tapeworms belonging to plant families 22 with greater dominance of the Lamiaceae family. The plants most cited were ginger, mastruz and mint, followed by garlic, heals all, boldo, basil, cashew, paregoric and orange elixir, with prevalence of tea as a form of preparation and sheet as most used plant part. Regarding the identification of parasitic and intestinal worms, found to roundworm (Ascaris lumbricoides), tuxina (Enterobius vermicularis) and ameba (Entamoeba histolytica) with the highest number of citations. It is worth mentioning that the residents surveyed also cited the conditions such as stomach pain, diarrhea, intestinal cramps, among others, as the most frequently treated with medicinal plants. Therefore, the study of plants to combat worms or parasites can contribute information needed to phytochemical and pharmacological studies for the formulation of new compounds.